2009
DOI: 10.1002/eji.200839026
|View full text |Cite
|
Sign up to set email alerts
|

Shine a light: Imaging the immune system

Abstract: Intra vital microscopy and whole-body imaging promise to revolutionize how we study the immune system. They compel by the intrinsic beauty of the images obtained and the undeniable direct biological relevance of the observations. However, it is important to remember that in many cases, fundamental insights into the underlying biological processes have already been obtained using ex vivo reductionist approaches. Indeed, it is likely that with the advent of microfluidics, new and exciting avenues will open up fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 146 publications
(150 reference statements)
0
4
0
Order By: Relevance
“…More examples and a detailed review of modern microscopic technologies used for imaging the immune system can be found in (283). Here we highlight some examples of the applications of the instruments and techniques mentioned above.…”
Section: Proteomicsmentioning
confidence: 99%
“…More examples and a detailed review of modern microscopic technologies used for imaging the immune system can be found in (283). Here we highlight some examples of the applications of the instruments and techniques mentioned above.…”
Section: Proteomicsmentioning
confidence: 99%
“…The array of microscopic techniques currently used to study immunology has recently been comprehensively summarized in an excellent review by Sarris and Betz [1]. Our report here will try to avoid too much overlap with this review.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidics also offer the means to create and maintain environments that closely resemble those encountered in vivo. 40,41 This is essential in ensuring that the experimental results are not biased with artefacts caused by, for example, early triggered apoptosis and, therefore, creating the right environment has important implications in cell analysis. Moreover, current microfabrication techniques allow the production of large arrays of microwells that can entrap single/multiple cells to perform molecular analysis, 42 or study cell response to chemical and physical stimuli following exposure to different environments; 43 the major advantage of this approach being the ability to perform parallel screening of a large number of cells.…”
Section: Applications In Biologymentioning
confidence: 99%